“Tekad” in Digital Art Creation Practice: Conceptual and Visual Exploration Using Procreate Software - Setiawan, Indra; Magfhirah, Permata Murni Bintang (V-art: Journal of Fine Art, 2025)
The creation of digital visual art in the contemporary era has evolved in tandem with technological advancements and creative software, enabling artists to explore ideas in more flexible and expressive ways. This article examines the practice of creating digital visual artworks themed “Tekad”, representing the values of determination, perseverance, and human resilience in confronting life’s challenges. The concept of tekad is interpreted through a personal and reflective perspective and subsequently translated into visual form through an exploratory approach to visual elements and design principles. This study employs a practice-based research method, positioning the artistic creation process as the primary source of knowledge. The stages of creation include conceptual formulation, visual reference exploration, digital sketch development, visualization processes, and final artwork completion using the Procreate application. Procreate is selected for its ability to simulate manual artistic techniques while offering digital flexibility in managing color, line, and texture. The results demonstrate that the concept of tekad can be powerfully articulated through visual symbolism, expressive line gestures, and color contrasts that reflect emotional tension and inner strength. The resulting artworks function not only as aesthetic representations but also as reflective media expressing inner experiences and humanistic values. This study is expected to contribute to the discourse on digital visual art creation, particularly in the utilization of Procreate as a medium for conceptual and artistic expression.